2020
DOI: 10.23860/jmle-2020-12-2-6
|View full text |Cite
|
Sign up to set email alerts
|

Can middle schoolers learn to read the web like experts? Possibilities and limits of a strategy-based intervention

Abstract: Can middle schoolers learn to read the web like experts? Possibilities and limits of a strategy-based intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 25 publications
(30 reference statements)
1
16
0
1
Order By: Relevance
“…Our findings contribute to a growing body of evidence that shows that students can improve their online reasoning by learning a few easy-to-apply heuristics drawn from research with professional fact checkers. Positive results have accrued across age levels: middle school (Kohnen et al, 2020), high school (Axelsson et al, 2021; McGrew, 2020; Pavlounis et al, 2021), college (Breakstone, Smith, Connors, et al, 2021; Brodsky, Brooks, Scimeca, Galati, et al, 2021; Brodsky, Brooks, Scimeca, Todorova, et al, 2021; McGrew et al, 2019), and adulthood (Panizza et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Our findings contribute to a growing body of evidence that shows that students can improve their online reasoning by learning a few easy-to-apply heuristics drawn from research with professional fact checkers. Positive results have accrued across age levels: middle school (Kohnen et al, 2020), high school (Axelsson et al, 2021; McGrew, 2020; Pavlounis et al, 2021), college (Breakstone, Smith, Connors, et al, 2021; Brodsky, Brooks, Scimeca, Galati, et al, 2021; Brodsky, Brooks, Scimeca, Todorova, et al, 2021; McGrew et al, 2019), and adulthood (Panizza et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…A much greater investment in research and development is needed to prepare students to navigate treacherous digital terrain. Small-scale but promising studies suggest that it is possible to improve students' digital savvy (Breakstone et al, 2021;Brodsky et al, 2019;Kohnen et al, 2020;McGrew, 2020;McGrew et al, 2019). Given the threat to civic and public health posed by digital illiteracy, these preliminary interventions need to be taken up at scale to identify approaches that can be widely adopted.…”
Section: Discussionmentioning
confidence: 99%
“…Their strategies guided our development of curriculum for evaluating online sources. To date, interventions based on fact checkers' strategies have yielded promising results across a wide age span: middle school (Kohnen et al, 2020), high school (McGrew, 2020;, and college (Brodsky et al, 2019;Fielding, 2019;McGrew et al, 2019;Supiano, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…• Prior interventions have shown that middle school, high school, and college students can become more skilled evaluators of digital content through in-person instruction when taught strategies used by professional fact checkers (Brodsky et al, 2019;Kohnen et al, 2020;McGrew, 2020;McGrew et al, 2019;Wineburg & McGrew, 2017. This study tested whether these strategies could be taught in an asynchronous college course.…”
Section: Essay Summarymentioning
confidence: 99%